Controlling anisotropic properties by manipulating the orientation of chiral small molecules - Wade, J; Salerno, F; Kilbride, RC; Kim, DK; Schmidt, JA; Smith, JA; LeBlanc, LM; Wolpert, EH; Adeleke, AA; Johnson, ER; Nelson, J; Mori, T; et al. (Springer Nature, 2022)
Chiral π-conjugated molecules bring new functionality to technological applications and represent an exciting, rapidly expanding area of research. Their functional properties, such as the absorption and emission of circularly polarized light or the transport of spin-polarized electrons, are highly anisotropic. As a result, the orientation of chiral molecules critically determines the functionality and efficiency of chiral devices. Here we present a strategy to control the orientation of a small chiral molecule (2,2'-dicyano[6]helicene) by the use of organic and inorganic templating layers. Such templating layers can either force 2,2'-dicyano[6]helicene to adopt a face-on orientation and self-assemble into upright supramolecular columns oriented with their helical axis perpendicular to the substrate, or an edge-on orientation with parallel-lying supramolecular columns. Through such control, we show that low- and high-energy chiroptical responses can be independently 'turned on' or 'turned off'. The templating methodologies described here provide a simple way to engineer orientational control and, by association, anisotropic functional properties of chiral molecular systems for a range of emerging technologies.